Entrepreneurial leadership and employee creativity: Moderation and mediation perspectives - Aristana, I Nengah; Wisnawa, I Made Bayu; Sriasih, Anak Agung Ketut; Junipisa, Ni Made Ernila (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This research aims to analyze and explain the influence of entrepreneurial leadership, information technology and employee creativity and to examine the role of knowledge sharing as the moderator and information technology as the mediator. The population in this research was all the small and medium enterprises engaged in handicrafts in Bali, amounting to 42 businesses. The determination of the sample was done by using a proportional sampling method involving leaders, supervisors and employees and the total sample in this research was 126 people. The result of this study indicates that entrepreneurial leadership has no significant, positive effect on employee creativity. Meanwhile, entrepreneurial leadership has a significant, positive effect on information technology. Information and knowledge sharing directly have a positive and significant effect on employee creativity. The moderating role of knowledge sharing has been proven to moderate the influence of entrepreneurial leadership on employee creativity, but the role shown has a weakening tendency. Meanwhile, knowledge sharing is not proven as moderating the influence of information technology on employee creativity. Information technology is proven to be a full mediation (fully mediating) the influence of entrepreneurial leadership on employee creativity.